G protein βγ regulation of KCNQ-encoded voltage-dependent K channels - Stott, Jennifer B.; Greenwood, Iain A. (Frontiers in Physiology, 2024)
The KCNQ family is comprised of 5 genes and the expression products form voltagegated potassium channels (Kv7.1-7.5) that have a major impact upon cellular physiology in many cell types. Each functional Kv7 channel forms as a tetramer that often associates with proteins encoded by the KCNE gene family (KCNE1-5) and is critically reliant upon binding of phosphatidylinositol bisphosphate (PIP2) and calmodulin. Other modulators like A-kinase anchoring proteins, ubiquitin ligases and Ca-calmodulin kinase II alter Kv7 channel function and trafficking in an isoform specific manner. It has now been identified that for Kv7.4, G protein βγ subunits (Gβγ) can be added to the list of key regulators and is paramount for channel activity. This article provides an overview of this nascent field of research, highlighting themes and directions for future study.